Ἁδριανὸς ἀνέθηκε: a Dedication by Hadrian in Arcadia - Kouremenos, Anna; Daubner, Frank (Tekmeria, 2025)
An intriguing inscription bearing the words Ἁδριανὸς ἀνέθηκε (Hadrian dedicated) appears in Inscriptiones Graecae (IG) and is the only example in the Greek world of this specific formula. Since the mid-nineteenth century, the inscription has been misattributed to an island, but our research reveals that it originated from a village near Tegea in Arcadia. Ancient literary sources and epigraphy confirm Hadrian’s active presence in Arcadia, where he made various dedications. But what exactly did he dedicate in this case? The inscription’s findspot –near a major road network and a site of multiple sanctuaries– offers clues about the nature of the emperor’s dedication. The formula suggests that the dedicated object was likely a statue or portable votive item, possibly accompanied by an epigram composed by Hadrian himself. This aligns with his well-documented habit of offering gifts and composing epigrams for sites of historical and religious significance. Thus, this inscription provides a rare glimpse into Hadrian’s personal role in dedications, preserving the only known instance of this dedication formula.